PERENCANAAN MODEL BISNIS PADA UPAYA KONVERSI BUS LISTRIK TRANS JOGJA - Hartanti, Sri; Wibisono, Muh. Arif (Politeknik Negeri Banyuwangi, 2024)
Indonesia currently has an oversupply of electricity. Until 2023 PLN has a remaining oversupply of around 6.1 thousand GWh. The cause is the 35-gigawatt coal-fired power plant megaproject. Economic growth has never reached 7%, but an average of 5%. While electricity growth, which was originally planned to reach 8%, the realization could not reach 5%. As a result, there was an oversupply of up to 1gigawatt, and PLN lost 3 trillion. Efforts are needed to increase electrification to reduce losses from oversupply. This is in accordance with the Yogyakarta Special Region Government's plan to convert Trans Jogja Buses into electric buses. This study aims to plan a business model for the conversion of Trans Jogja Buses to Electric Buses, and analyze the feasibility of its investment. From the four business models given, business model 2 was obtained as the best scenario. In this model, Dinas Perhubungan Yogyakarta as the owner of the electric bus fleet and charging station, then contracts the operator PT Anindya Mitra Internasional to be responsible for the operation, while the maintenance of the fleet is carried out by the Original Equipment Manufacturer (OEM). Business model 2 has the highest NPV, which is Rp212,801,776,072 indicating that this project generates greater value compared to the other business models. Other that, business model 2 has an Internal Rate of Return (IRR) of 17%, which is higher than business model 1 and business model 3, indicating a higher potential return on investment. The Payback Period (PBP) is similar to business model 1, which is 4 years and 2 months, but overall the business model 2 project is more profitable. So business model 2 is the best option to implement.